EFEITO TRÓFICO DA OUABAÍNA EM NEURÔNIOS CENTRAIS - Corrêa, Gustavo de Rezende (2009)
Ouabain is a digitalic steroid hormone that inhibits Na+, K+ - ATPase activity. However, during the last years, it has been proposed that Na+, K+ - ATPase acts as a membrane receptor being endogenous ouabain its physiological ligand. Data from literature shows the effect of ouabain controlling growth, proliferation and cell survival. The aim of this work was to study ouabain (3.0nM) signaling pathways involved in the increase of rat retinal ganglion cell survival. Our results show that the ouabain effect can be observed up to 96 hours in culture and is mediated by EGF receptor transactivation via Src. The signaling pathway involves the activation of PLC, PKCd and JNK since tyrfostin 2.5µM, PP1 1.0µM, U73122 4µM, rottlerin 2.0µM and iJNK 0.5 1.0µM respectively abolished the ouabain effect. We also observed by immunofluorescence that after 15 minutes of ouabain treatment the PKCd activation is already observed. Interestingly, a synergistic effect was obtained when the cultures were treated with both ouabain (0.75nM) and BDNF (10ng/mL). Our results suggest that ouabain plays a trophic role controlling the survival of retinal ganglion cells.